THERMAL CONDUCTIVITY TEST VALUE BATAKO HOLLOW WITH RICE HUSK - Rahmaniah, Rahmaniah; Akmal, Akmal; Said L, Muh. (Teknosains: Media Informasi Sains dan Teknologi, 2015)
Has been conducted research on the measurement of the thermal conductivity in the sample hollow Batako and batako samples has been filled rice husk. this research aimed to determine the effect of temperature changes on two different sample types. In this research first conducted calorific value calculation on two different sample types. Then performed the calculation of the conductivity value then the conductivity values obtained were compared with the theoretical value of conductivity. Measurement of the temperature value must be checked every 10 minutes for 6 hours per day within 12 days. The results showed that the role of rice husk in the heat absorption system is very influential. The temperature batako Sample are not filled rice husk increased faster than rice husk filled bricks so that the value of the temperature change will also affect which will affect the calculation of calorific value. Value of temperature changes on hollow batako smaller if compared with batako stuffed rice husk. Calculation of calorific value in the hollow batako samples obtained calorific values for the lamp 25 W of 18.339 J and batako samples were filled rice husks for lamp 25 W at 17.226 J. While the calorific value of the lamp 40 W for the sample is 28.839 A hollow batako and batako samples were filled husks calorific value of 33.019 A. The conductivity values obtained in the two different types batako samples is 0.339 W/moC or in other words equal to the value batako thermal conductivity according to the theory. Test values obtained greater mechanical stress on the batako samplefilled rice husk compared with hollow batako samples.